Enhancement of Productivity, Profitability and Resource Use Efficiency of Rice-rapeseed Cropping System through Liming, Planting Time and Tillage Practices in North East India - Sorokhaibam, Sakhen; Singh, N. Anando; Nabachandra, L. (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted during 2010−12 to study the effect of liming, planting time and tillage on system productivity, profitability and resource use efficiency of rice (Oryza sativa L.) - rapeseed (Brassica campestris L.var. toria) cropping system. The experiment was laid out in a split plot design with two factors i.e. liming (liming and no liming) and planting time (early and normal) given to rice crop during rainy (kharif) season in the main plots and 2 tillage practices (no tillage and conventional tillage) given to succeeding rapeseed during the winter (rabi) season in sub-plots. Application of lime @ 500 kg CaCO3 ha-1 before planting rice continuously for two cropping seasons had residual effect on seed and stover yields of succeeding rapeseed resulting in improvement of system productivity in terms of rice equivalent yield (REY), production efficiency (PE) and water use efficiency (WUE) by 7.2%, 7.4% and 11.1%, respectively over no liming. Liming failed to increase B:C ratio but enhanced energy productivity by 3.7% over no liming. Early planting of rice 15 days ahead of normal planting time enhanced growth and yield of rapeseed crop and had registered significantly higher REY, land use efficiency (LUE), PE, WUE, NPK nutrient use efficiencies, net returns and energy use efficiency compared to normal planting. No tillage (NT) enhanced REY, NPK use efficiencies, WUE and B:C ratio of the system. NT was the most energy efficient practice with 14.6% less energy requirement as compared to conventional tillage (CT).